Winter and early spring assemblages of ladybird beetles (Coleoptera: Coccinellidae) in two forest habitats in suburban area of Warsaw, central Poland - Bodzon, Karolina; Ceryngier, Piotr (Studia Ecologiae et Bioethicae, 2016)
In March and April of 2014 and 2015, overwintering and post-overwintering assemblages of ladybird beetles were investigated in deciduous (Tilio-Carpinetum) and mixed forest (Querco roboris-Pinetum) patches in a forest complex on the north-western periphery of Warsaw. March samples were collected by sifting forest litter with an entomological sieve, while in April, ladybirds were collected from the vegetation using sweeping net and beating sheet. In both years, mean densities of ladybirds found in March in the two forest types were low, not exceeding 2 individuals/m2. Seven ladybird species were found overwintering in the litter of the deciduous forest and four in that of the mixed forest. Propylea quatuordecimpunctata was the most abundant in both habitats in 2014, while in 2015 in the litter of the deciduous forest Vibidia duodecimguttata predominated. In April, 15 species were recorded in the deciduous forest and 7 in the mixed forest. Scymnus ferrugatus predominated in the former plant community and P. quatuordecimpunctata and Coccinella septempunctata in the latter. Several of the recorded species, such as Clitostethus arcuatus, Scymnus femoralis and S. abietis, have rarely been reported from Poland.